BS01. Facial twitching: Hemifacial spasms or seizures?. (May 2018) - Khan, Tasleema; Jayakody, Himali; Maciver, Stephanie; Benbadis, Selim R.
Abstract : Introduction: Not everything that twitches is a seizure, and isolated hemifacial twitching with no other symptoms can be a diagnostic challenge. We present a case of facial twitching that was initially thought to be hemifacial spasm, only to have the diagnosis changed to focal motor seizures with the aid of EEG-video monitoring. Methods: The patient is a 20-year-old man who presented with new episodes of facial twitching. He carried a diagnosis of mitochondrial disease and epilepsy. At the age of 13, he had his first generalized tonic-clonic seizure, and these have been well controlled for over 3 years. He presented with a 5-week history of left facial twitching and was admitted for long term video monitoring to characterize events. Results: Within minutes of EEG being hooked up, patient had mild hemifacial twitching involving both the upper and lower face (corner of the eye and the corner of the lips) on the left side, which spontaneously resolved within 45 s. He continued to have multiple episodes, without any loss of awareness. On EEG, there were no abnormal changes, and there were also no interictal discharges. Initially, this was most suggestive of hemifacial spasms. Overnight, the twitching occurred in sleep (mainly N2 sleep) and became more pronounced, frequent, clearly clonic in nature, and spread to involve the right side of his face. He continued to maintain awareness and was able to talk and follow commands during the events. The EEG still did not reveal epileptiform discharges, ictally or interictally, but showed muscle artifact that evolved in an epileptic pattern. The pattern was rhythmic, with gradual increase in frequency followed by slowing prior to ending abruptly. All these features supported the diagnosis of seizures. Conclusion: This is an example of a complex case of hemifacial twitching that with initial presentation appeared to be hemifacial spasm. It is important to note there were no epileptiform discharges or interictal pattern to suggest a diagnosis of seizures throughout the entire recording, and this is often the case with small, partial, motor seizures. As it is often, video was key as it allowed observation of the evolution, both electrographically (EMG) and clinically, which led to diagnosis of seizures.